Pengaruh Teman Sebaya terhadap Karakter Sosial Siswa pada Pembelajaran PAI di SMPN 2 Sungai Pua - Tasya Anggraini; Jasmienti Jasmienti (YASIN, 2026)
Although studies on student character formation have been widely conducted, research that specifically discusses the influence of peers on students’ social character in the context of Islamic Religious Education (PAI) learning remains relatively limited. This study aims to analyze the influence of peers on students’ social character in seventh-grade PAI learning at SMPN 2 Sungai Pua. This study employed a quantitative approach with a correlational survey design, involving 22 students as respondents selected through the total sampling technique. The research data were collected through a questionnaire measuring the peer and students’ social character variables, and were then analyzed using simple linear regression with the assistance of statistical software. The results showed a positive and significant influence between peers and students’ social character. This was indicated by a correlation coefficient value of R = 0.860, which suggests a very strong relationship, as well as a significance value of 0.000 (p < 0.05). In addition, the coefficient of determination (R²) value of 0.739 indicates that peers contributed 73.9% to students’ social character, while the remaining 26.1% was influenced by other factors outside this study. These findings emphasize that positive interaction with peers has an important role in shaping students’ social character in the school environment. The implications of this study indicate the importance of the role of teachers and schools in creating a healthy and constructive social environment to support the strengthening of student character education.